Bone Marrow Mesenchymal Stem Cells Ameliorates Seawater-Exposure-Induced Acute Lung Injury by Inhibiting Autophagy in Lung Tissue. (19th August 2014) - Liu, Qiu-ping; Zhou, Dang-xia; Sun, Li; Ling, Luo; Wu, Chang-gui; Lin, Pu; Han, Shui-ping
Abstract : Seawater drowning can lead to acute lung injury (ALI). Several studies have shown that bone marrow mesenchymal stem cells (BMSC) treatment could attenuate ALI. However, the mechanisms underlying this phenomenon still remain elusive. Therefore, this study aimed to investigate whether BMSC treatment can ameliorate seawater-induced ALI and its underlying mechanisms in a rat model. In this study, arterial blood gas, lung weight coefficient, and TNF- α, and IL-8 in bronchoalveolar lavage fluid (BALF), as well as histopathology examination, were used to detect the lung injury of seawater exposure. Moreover, western blot and RT-PCR were used to explore autophagy in lung tissues. The results demonstrated that seawater exposure induced ALI including impaired arterial blood gas, pulmonary edema, histopathologic changes, and inflammatory response in lung tissues. What is more, these changes were partly ameliorated by BMSC treatment through inhibition of autophagy in lung tissues. The application of BMSC may be a potential effective treatment for seawater-induced ALI.